Evolution of SARS-CoV-2: BA.4/BA.5 Variants Continues to Pose New Challenges - Quadir, Neha; Singh, Jasdeep; Alam, Anwar; Malik, Asrar Ahmad; Rahman, Syed Asad; Hira, Subhash; Ehtesham, Nasreen Zafar; Sundar, Durai; Hasnain, Seyed Ehtesham (Viruses, 2022)
The acquisition of a high number of mutations, notably, the gain of two mutations L452R and F486V in RBD, and the ability to evade vaccine/natural infection-induced immunity suggests that Omicron is continuing to use “immune-escape potential” as an evolutionary space to maintain a selection advantage within the population. Despite the low hospitalizations and lower death rate, the surges by these variants may offset public health measures and disrupt health care facilities as seen recently in Portugal and the USA. Interestingly these BA.4/BA.5 variants have been found to be more severe than the earlier-emerged Omicron variants. We believe that aggressive COVID-19 surveillance using affordable testing strategies might actually help understand the evolution and transmission pattern of new variants. The sudden dip in reporting of new cases in some of the low- and middle-income countries is an alarming situation and needs to be addressed as this could lead to undetected transmission of future variants of interest/concern of SARS-CoV-2 in large population settings, including advent of a ‘super’ virus. It would be interesting to examine the possible role/influence, if any, of the two different kinds of vaccines, the spike protein-based versus the inactivated whole virus, in the evolution of BA.4/BA.5.